A simplified methodology for risk analysis of historic centers: the world heritage site of San Gimignano, Italy. Issue 3 (11th February 2021) - Giuliani, Francesca; De Falco, Anna; Cutini, Valerio; Di Sivo, Michele
Abstract : Purpose: Worldwide, natural hazards are affecting urban cultural heritage and World Heritage Sites, exacerbating other environmental and human-induced threats deriving from deterioration, uncontrolled urbanization and unsustainable tourism. This paper aims to develop a disaster risk analysis in Italian historic centers because they are complex large-scale systems that are cultural and economic resources for the country, as well as fragile areas. Design/methodology/approach: A heritage-oriented qualitative methodology for risk assessment is proposed based upon the formalization of risk as a function of hazard, vulnerability and exposure, taking into account the values of cultural heritage assets. Findings: This work provides a contribution to the body of knowledge in the Italian context of disaster risk mitigation on World Heritage Sites, opening for further research on the monitoring and maintenance of the tangible heritage assets. The application to the site of San Gimignano proves the effectiveness of the methodology for proposing preventive measures and actions that ensure the preservation of cultural values and a safer built environment. Originality/value: The application of a value-based simplified approach to risk analysis is a novelty for historic centers that are listed as World Heritage Sites.